Historical tide gauge sea‐level observations in Alicante and Santander (Spain) since the 19th century. (1st January 2021) - Marcos, Marta; Puyol, Bernat; Amores, Angel; Pérez Gómez, Begoña; Fraile, María Ángeles; Talke, Stefan Andreas
Abstract: A set of historical tide gauge sea‐level records from two locations in Santander (Northern Spain) and Alicante (Spanish Mediterranean coast) have been recovered from logbooks stored in national archives. Sea‐level measurements have been digitized, quality‐controlled and merged into three consistent sea‐level time series (two in Alicante and one in Santander) using high‐precision levelling information. The historical sea‐level record in Santander consists of a daily time series spanning the period 1876‐1924 and it is further connected to the record from the modern tide gauge station nearby, ensuring datum continuity up to the present. The sea‐level recording in Alicante started in 1870, with daily averaged values until the 1920s and hourly afterwards, and the tide gauges at the two Alicante sites are still operating, thereby providing one of the longest tide gauge sea‐level time series in the Mediterranean Sea. The long‐term consistency and reliability of the new records are discussed based on comparison with nearby tide gauge time series. Abstract : Pictures of the tide gauges used at Santander and Alicante: Adie floating gauge (a) and Mier syphon tide gauge (a) and Thomson floating gauge (b).